TRANSFER OF TECHNOLOGY – MECHANISM OF MODERN UNIVERSITY WITH COMMUNITY CONNECTION - Mihaela DIACONU; Amalia DUTU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2014)
This study presents, starting from the third mission of the university, a modern mechanism – technology transfer, by which the university can effectively contribute to local and regional socio-economic development and may provide additional sources of income for the research and development work in terms of substantially reducing the financial support by the state. The study emphasizes the role of the office of technology transfer as a means of connection of the university with the business environment able to arrange joint efforts of both sides in economic development. The method used was that of thematic analysis of the content of data published on the websites of the best performing TTO`s on technology transfer and the literature referring to the third mission of the university. The study develops a methodology with the procedural approach and the steps that should followed so that the university could become more competitive with the help of TTO. The conclusion is that, in the current conditions of higher education market, the entrepreneurial spirit of the university valued through TTO brings important benefits to society.